Bioprospecting of inhibitors of EPEC virulence from metabolites of marine actinobacteria from the Arctic Sea - Pylkkö, Tuomas; Schneider, Yannik Karl-Heinz; Rämä, Teppo; Andersen, Jeanette Hammer; Tammela, Päivi (Frontiers in Microbiology, 2024)
A considerable number of antibacterial agents are derived from bacterial metabolites. Similarly, numerous known compounds that impede bacterial virulence stem from bacterial metabolites. Enteropathogenic Escherichia coli (EPEC) is a notable human pathogen causing intestinal infections, particularly affecting infant mortality in developing regions. These infections are characterized by microvilli effacement and intestinal epithelial lesions linked with aberrant actin polymerization. This study aimed to identify potential antivirulence compounds for EPEC infections among bacterial metabolites harvested from marine actinobacteria (Kocuria sp. and Rhodococcus spp.) from the Arctic Sea by the application of virulence-based screening assays. Moreover, we demonstrate the suitability of these antivirulence assays to screen actinobacteria extract fractions for the bioassayguided identification of metabolites. We discovered a compound in the fifth fraction of a Kocuria strain that interferes with EPEC-induced actin polymerization without affecting growth. Furthermore, a growth-inhibiting compound was identified in the fifth fraction of a Rhodococcus strain. Our findings include the bioassay-guided identification, HPLC-MS-based dereplication, and isolation of a large phospholipid and a likely antimicrobial peptide, demonstrating the usefulness of this approach in screening for compounds capable of inhibiting EPEC virulence.